ANALISIS KOMPARATIF TERHADAP PENDAPATAN PETANI DAN PENAMPILAN PASAR TEMBAKAU KASTURI DESA SUMBERPINANG KECAMATAN PAKUSARI KABUPATEN JEMBER - Ni Wayan Yekha Sudiasih; Sugeng Raharto; Julian Adam Rijal (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
Sumberpinang Village, Pakusari Subdistrict is one of the producers of Kasturi tobacco in District of Jember.. Kasturi tobacco is a contributor to one of the country's foreign exchange in the plantation sector and cultivated by farmers in Jember. This study aims to determine (1) The differences in the revenue of farmers who sell “tebasan, setengah kering/kerosok, untingan”, (2) The market performance Kasturi tobacco, (3) The level of equity of market participants of Kasturi tobacco. Determination of the study area is done intentionally (purposive method) i.e. Sumberpinang. Methods Descriptive, comparative, and analytical method is the method used in conducting this research. The method of analysis used is the analysis of farmers' revenue, followed by one-way ANOVA test, analysis of marketing margins, efficiency of marketing, price transmission elasticity, share profits and costs and chi-square distribution analysis. The research states that (1) There are differences in the revenue of farmers in all three of Kasturi tobacco sales, (2) Marketing of Kasturi tobacco at Sumberpinang is not efficient (3) Average percentage of profits is not same with the average percentage of costs for each marketing agencies.